Analisis Pengelolaan Alokasi Dana Desa (ADD) Di Kecamatan Mare Kabupaten Bone - Tikollah, M. Ridwan; A. Ngampo, M. Yusuf (Universitas Negeri Makassar, 2018)
The research is aimed to detemine the management of Alokasi Dana Desa (ADD) in Mare Subdistrict Bone Regency. which include: planning, implementation, administration, reporting, dan accountability. The population of this research were all Village Government and its apparatus and accountability report of APBDes Mare Subdistrict Bone Regency a number of 17 villages. The sample of the study was chosen by purposive sampling with the criteria: (1) the village receiving the highest ADD, (2) the village receiving the lowest ADD, (3) the village located in the capital city of Mare Subdistrict, (4) the nearest village of the capital city of Mare Subdistrict, and (5) the farthest village from the capital city of Mare Subdistrict. Based on the criteria, five villages were chosen: Batu Gading Village, Data Village, Mario Village, Lappa Upang Village, and Kadai Village. The data were collected by questionnaire and documentation. The data obtained were analyzed using descriptive-comparative method with percentage of crude index agreement (indeks kesesuaian kasar/IKK). The results of this research suggest that the management of ADD which includes: planning, implementation, administration, reporting, and accountability with 63 indicators in Mare Subdistrict Bone Regency has been in accordance with Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 tentang Pengelolaan Keuangan Desa.